Intertextual relationships between “Alienación”, a short story by Julio Ramón Ribeyro, and “Alienación”, a short film by Alex Fischman - Leonardo-Loayza, Richard (Universidad Pedagógica y Tecnológica de Colombia, 2021)
Cinema and literature have close relationships, among which adaptations stand out. To study the latter, the criterion of elucidating whether or not the filmic text is faithful to the literary  text has been used. One way to develop this analysis is through intertextuality. However, other theoretical contributions complement this perspective, such as Genette’s transtextuality or Doležel’s transduction. In the article we apply these categories to address the relationships that are established between the short story “Alienación” (1975), by Julio Ramón Ribeyroand the short film “Alienación” (2019) by Alex Fischman. We are interested in establishing  whether Fischman’s text is just a staging of Ribeyro’s story, or, instead, he comes to resignify the original text to the point of turning it into a different one.